The effect of Calcium-D3 Nicomed drug on strength properties of the bone tissue in rats - Karpinsky, Mykhaylo; Umarov, Fayzulla; Ivanov, Gennadiy; Karpinska, Olena; Subbota, Igor; Tyazhelov, Olexiy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
The article describes results of experimental studies of firmness properties of the humeri in rats after a modelled metaphyseal fracture and treatment of the animals with Calcium-D3 Nicomed drug. The use of Calcium-D3 Nicomed drug in the process of treating skeletal bone fractures of rats made it possible to increase firmness of the osseous tissue on both the injured and contralateral extremities.